CAPITALA VĂZUTĂ PRIN PRISMA PROGRAMELOR DE ANIMAȚIE - TRICOLICI, bibliotecar principal, Departamentul „Memoria Chișinăului”, Claudia (BIBLIOPOLIS, 2020)
The paper is about the library activities dedicated to the our city, Chisinau, held between 4-14 of December 2015 at the B.P. Hasdeu Municipal Library. The author presents the variaty of cultural activities, traditional and electronic, aiming the promotion and valorification of cultural heritage, highlights the implication of personalities from Chisinau: writers, actors, historians, phisicians etc. in city’s life.